On the safety of acetaminophen - R. N. Alyautdin; V. K. Lepakhin; B. K. Romanov; A. P. Pereverzev (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
Acetaminophen is one of the most commonly used analgesics /anti pyretics. However, taking into account the existing risk of hepatotoxicity,regulatory bodies of a number of the countries made additional adjustments tothe recommendations on the use of this drug. In the article the possible reasonsfor recourse to acetaminophen are discussed